Family functioning in psychogenic nonepileptic seizures: Qualitative study - Sneha Vinay Haritsa; Kalapalli Jayasankara Reddy; Meghna Gupta (Annals of Indian Psychiatry, 2023)
Background: Psychogenic nonepileptic seizures (PNES) are understood as epileptic presentations without a neurological basis. PNES has underlying psychological stressors that manifest physiologically. However, family functioning has been poorly studied despite its potential to be one of the major stressors. Few studies on family functioning have focused on differences between PNES and epileptic seizures than an in-depth inquiry into family functioning in PNES. Methods: Patients diagnosed with PNES by a psychiatrist or neurologist through home videos were chosen to participate in the study. Participants had at least one seizure in the previous week before the interview, and those who had physical disabilities or comorbid epilepsy were excluded from the study. In-depth interviews were developed and conducted. Determined data was analyzed through latent thematic analysis. Results: Based on the determined data, nine themes were identified. They included interaction and attachment, communication, structure and system, distressful family factors, expressed emotions, cultural aspects, maladaptive coping, adaptive coping, and negative emotional experience. Approach avoidance and hints of ending relationships were the types of communication among PNES patients, attachment has been inconclusive, transgenerational trauma, disengaged boundaries, coalition, and maladaptive triangles are prevalent among families of PNES patients. Over-involvement and hostility are the expressed emotions that were found. Both maladaptive and adaptive coping strategies are found among PNES patients. Finally, superstitions and beliefs in possession exist among families of PNES patients. Conclusion: Family dysfunction is prevalent among families of PNES patients, and hence, family-based interventions are necessary.